Pharmacokinetic Modelling of Efavirenz, Atazanavir, Lamivudine and Tenofovir in the Female Genital Tract of HIV-Infected Pre-Menopausal Women - Dumond, Julie B. (2012)
BACKGROUND AND OBJECTIVES: A previously published study of antiretroviral pharmacokinetics in the female genital tract of HIV-infected women demonstrated differing degrees of female genital tract penetration among antiretrovirals. These blood plasma (BP) and cervicovaginal fluid (CVF) data were co-modelled for four antiretrovirals with varying CVF exposures. METHODS: Six paired BP and CVF samples were collected over 24 h, and antiretroviral concentrations determined using validated liquid chromatography (LC) with UV detection or LC-mass spectrometry analytical methods. For each antiretroviral, a BP model was fit using Bayesian estimation (ADAPT5), followed by addition of a CVF model. The final model was chosen based on graphical and statistical output, and then non-linear mixed-effects modelling using S-ADAPT was performed. Population mean parameters and their variability are reported. Model-predicated area under the concentration-time curve during the dosing interval (AUC(τ)) and exposure ratios of CVF AUC(τ):BP AUC(τ) were calculated for each drug. RESULTS: The base model uses first-order absorption with a lag time, a two-compartment model, and a series of transit compartments that transfer the drug from BP to CVF. Protein-unbound drug transfers into CVF for efavirenz and atazanavir; total drug transfers for lamivudine and tenofovir. CVF follows a one-compartment model for efavirenz and atazanavir, and a two-compartment model for lamivudine and tenofovir. As expected, inter-individual variability was high. Model-predicted CVF AUC(τ):BP AUC(τ) ratios are consistent with published results. CONCLUSIONS: This is the first pharmacokinetic modelling of antiretroviral disposition in BP and CVF. These models will be further refined with tissue data, and used in clinical trials simulations to inform future studies of HIV pre-exposure prophylaxis in women.